1985
DOI: 10.1515/jpme.1985.13.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of hypoxanthine and lactate in the blood of healthy and hypoxic newborns

Abstract: Jung cl al., Hypoxanthine and lactate in newborns 43

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The hypoxanthine concentrations in cord blood of neonates after normal gestation and birth was similar to those found in neonates on the first day of life [7,9]. There was a considerable difference in the concentration of hypoxanthine we found in plasma from umbilical blood and that reported by other authors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The hypoxanthine concentrations in cord blood of neonates after normal gestation and birth was similar to those found in neonates on the first day of life [7,9]. There was a considerable difference in the concentration of hypoxanthine we found in plasma from umbilical blood and that reported by other authors.…”
Section: Discussionsupporting
confidence: 86%
“…Some authors have found a significant correlation between the concentration of hypoxanthine in blood from the scalp or the umbilical cord vessels of fetuses or neonates directly after delivery and biochemical parameters of hypoxia such as pH, base deficit, lactate concentration, Apgar score, and clinical hypoxia scores [8,16,17]. Other authors have found no such relationship [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…It should be men tioned that the high correlation coefficient found between blood lactate concentrations and pH in the control and hypoxic newborns (-0.980; p < 0.005 and -0.926; p < 0.05, respectively), together with the changes ob served in blood Pco2 suggest that acidosis is mainly due to the increase in lactate concen trations. In agreement with the result found in the human newborn [20], a significant corre lation (r = 0.93; p < 0.02) is observed between blood 'xanthines' and lactate concentrations in the hypoxic newborn rat ( fig. 1, 2).…”
Section: Animalssupporting
confidence: 90%
“…The correlation between hypoxanthine and lactate in eight hypoxic babies was r = 0.64, p < 0.001) (68). High hypoxanthine levels were measured in preterm babies with respiratory distress syndrome (RDS) and with congenital heart lesions (69,70).…”
Section: Animal Studiesmentioning
confidence: 97%